Influence of subinhibitory concentrations of amikacin and ciprofloxacin on morphology and adherence ability of uropathogenic strains - Wojnicz, D; Kłak, M; Adamski, R; Jankowski, S (Folia microbiologica, 2007)
The influence of subinhibitory concentrations (1/2, 1/4, 1/8, 1/16 and 1/32 MIC) of amikacin and ciprofloxacin on the morphology and adherence of uropathogenic strains was studied. Intensity of morphological changes was proportional to the concentrations of these antibiotics. Morphological changes were the most prominent after bacterial exposure to sub-MICs of ciprofloxacin. These concentrations, especially 1/2 MIC of ciprofloxacin, induced the formation of filaments of E. coli, K. pneumoniae, K. oxytoca, E. cloacae and A. calcoaceticus biotype anitratus. No morphological changes were observed in P. aeruginosa, S. epidermidis and S. aureus cells after exposure to subinhibitory concentrations of both antibiotics. Sub-MICs of amikacin affected the changes in cell shape only slightly. The exposure of bacterial strains to 1/2 MIC of ciprofloxacin induced increased vacuolation of the cells. We observed shrinkage of the protoplasm and the pleated cell walls in comparison with control cells. The greatest loss of adherence ability occurred at 1/2 MIC of ciprofloxacin after a 1-d incubation.
Keywords: Microbial Sensitivity Tests; enterobakteriální infekce; amikacin; Humans; infekce močového ústrojí; Microscopy, Phase-Contrast; Female; mikrobiální testy citlivosti; Anti-Infective Agents; Microscopy, Electron, Scanning; antiinfekční látky; epitelové buňky; lidé; Enterobacteriaceae Infections; Bacterial Adhesion; Enterobacteriaceae; mikroskopie fázově kontrastní; ciprofloxacin; bakteriální adheze; ženské pohlaví; Epithelial Cells; mikroskopie elektronová rastrovací; Ciprofloxacin; transmisní elektronová mikroskopie; Microscopy, Electron, Transmission; Urinary Tract Infections; Amikacin